Workshop Pemanfaatan AI untuk Meningkatkan Literasi Digital Guru-Guru SMK dalam Proses Pembelajaran di Sekolah - Achmad Daengs GS; Ni Luh Wiwik Sri Rahayu Ginantra; Teuku Afriliansyah; Anjar Wanto; Harly Okprana (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
This activity aims to equip UISU Siantar Private Vocational School teachers with knowledge and skills in utilizing Artificial Intelligence (AI) to increase learning effectiveness. This activity was carried out over two days with various sessions, including basic AI theory, the use of AI applications in learning, and direct practice in implementing AI in the classroom. The activity focuses on implementing AI workshops to increase vocational school teachers' digital literacy, especially at UISU Siantar Private Vocational School. This program is driven by rapid technological developments and the need to improve the quality of education through the integration of advanced technology, as well as equipping vocational school teachers with knowledge and skills in utilizing AI for various aspects of learning, including curriculum design, student evaluation, and classroom management. The team delivered the activity workshop in 2 ways, face-to-face and virtual, via the Zoom application. A pre-test and post-test were carried out on participants to measure the workshop's effectiveness. The average pre-test score was 60, while the average post-test score increased to 71.9. The analysis results show a significant increase in the level of teacher understanding. This increase indicates that the workshop successfully increased the digital literacy of vocational school teachers so that they are better prepared to integrate AI technology into the learning process at school.